Performance Of State Civil Apparatus: Intervening Effects Of Organizational Commitment And Work Motivation - Muhammad Ikram Idrus; Muhammad Islah Idrus (International Journal of Artificial Intelligence Research, 2024)
The performance of an  employee in a  government agency can be known from the results of a job  which can be shown by the degree of the employee's ability to complete a job.  The purpose of  this  study is toanalyze the direct influence of competence on organizational commitment,  work motivation and employee performance of the South Sulawesi Provincial Marine and Fisheries Service both directly and indirectly. The type of research used is a quantitative research method  with data collection using a questionnaire. This research was conducted using a survey approach and distributing questionnaires to analyze facts and data that support the information needed to support the discussion of the research. Thecausal relationship between the variables was obtained through hypothesis testing using SPSS and SmartPLS.  The results showed that partially, competence has a positive and significant effect  on organizational commitment,  work motivation and  employee performance.  Furthermore, organizational commitment has  an insignificant  effect on employee performance  while work motivation has a positive and significant impact  on employee performance  . As for indirect influence  , it shows that organizational commitment has an  insignificant effect   when used as a mediating variable  the influence of  competence on performance while motivation is able to show   positive and significant influence when used as a mediating variable